Analysis of third-party fund management strategies in supporting sustainable financing growth at Bank Sumut Syariah Binjai Sub-Branch - Ika Damai Sari; Nurlaila Nurlaila; Yusrizal Yusrizal (Indonesia Auditing Research Journal, 2026)
This study aims to analyze Third-Party Fund management strategies in supporting financing growth at Bank Sumut Syariah Binjai Sub-Branch. The study employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model and BCG Matrix approach. The results showed that relationship marketing and service quality improvement strategies in supporting the collection of third party funds and the growth of islamic bank financing. Financing distribution increased during the 2021–2025 period; however, the growth of Third-Party Funds tended to fluctuate, resulting in an increase in the Financing to Deposit Ratio and Non-Performing Financing. Overall, the Third-Party Fund management strategies have supported financing growth, but their effectiveness still needs to be improved to maintain funding stability and the sustainability of bank performance.